Germany : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
The study on selected issues first focuses on business fixed investment, then analyzes the profitability of Germany's banking sector and looks at restructuring options, and finally, examines the international dimensions of Germany's financial sector. The paper reviews the various ways in which public policy could contribute to restructuring, drawing on the experiences of other countries that have had large public banking sectors. There is no evidence that either recent tax reforms or weak U.S. growth has had a significant independent impact on investment.